β-Glucan Size Controls Dectin-1-Mediated Immune Responses in Human Dendritic Cells by Regulating IL-1β Production - Elder, Matthew J.; Webster, Steve J.; Chee, Ronnie; Williams, David L.; Hill Gaston, J. S.; Goodall, Jane C. (Frontiers in Immunology, 2017)
Dectin-1/CLEC7A is a pattern recognition receptor that recognises β-1,3 glucans, and its stimulation initiates signalling events characterised by the production of inflammatory cytokines from human dendritic cells (DC) required for anti-fungal immunity. β-glucans differ greatly in size, structure and ability to activate effector immune responses from DC; as such, small particulate β-glucans are thought to be poor activators of innate immunity. We show that β-glucan particle size is a critical factor contributing to the secretion of cytokines from human DC; large β-glucan-stimulated DC generate significantly more IL-1β, IL-6 and IL-23 compared to those stimulated with the smaller β-glucans. In marked contrast the secretion of TSLP and CCL22, were found to be insensitive to β-glucan particle size. Furthermore, we show that the capacity to induce phagocytosis, and the relative IL-1β production determined by β-glucan size, regulates the composition of the cytokine milieu generated from DC. This suggests that β-glucan particle size is critically important in orchestrating the nature of the immune response to fungi.